Analysis of the Phlebiopsis gigantea genome, transcriptome and secretome provides insight into its pioneer colonization strategies of wood. - Chiaki Hori; Takuya Ishida; Kiyohiko Igarashi; Masahiro Samejima; Hitoshi Suzuki; Emma Master; Patricia Ferreira; Francisco J Ruiz-Dueñas; Benjamin Held; Paulo Canessa; Luis F Larrondo; Monika Schmoll; et al. (PLoS Genetics, 2014)
Collectively classified as white-rot fungi, certain basidiomycetes efficiently degrade the major structural polymers of wood cell walls. A small subset of these Agaricomycetes, exemplified by Phlebiopsis gigantea, is capable of colonizing freshly exposed conifer sapwood despite its high content of extractives, which retards the establishment of other fungal species. The mechanism(s) by which P. gigantea tolerates and metabolizes resinous compounds have not been explored. Here, we report the annotated P. gigantea genome and compare profiles of its transcriptome and secretome when cultured on fresh-cut versus solvent-extracted loblolly pine wood. The P. gigantea genome contains a conventional repertoire of hydrolase genes involved in cellulose/hemicellulose degradation, whose patterns of expression were relatively unperturbed by the absence of extractives. The expression of genes typically ascribed to lignin degradation was also largely unaffected. In contrast, genes likely involved in the transformation and detoxification of wood extractives were highly induced in its presence. Their products included an ABC transporter, lipases, cytochrome P450s, glutathione S-transferase and aldehyde dehydrogenase. Other regulated genes of unknown function and several constitutively expressed genes are also likely involved in P. gigantea's extractives metabolism. These results contribute to our fundamental understanding of pioneer colonization of conifer wood and provide insight into the diverse chemistries employed by fungi in carbon cycling processes.